INFLUENCERS: THE IMPORTANCE OF PERSONAL BRANDING ON INSTAGRAM - Muflih, Hafizh; Fikriyasin, Cikal Aji; Falah, Muhammad Bilal; Imawan, Khaerudin; Erawati, Dedet (International Journal of Social Service and Research, 2024)
In the era of globalization, social media is considered an effective tool of mass communication. In this study, a qualitative approach is employed to analyze the Instagram account of Gantar Surapati using a visual approach methodology. The results show that the visual communication techniques employed in this study are essential for understanding, reading, and interpreting the meaning behind images, photographs, videos, and other forms of visual communication. The research demonstrates how content can shape a positive personal brand and provides practical guidance for influencers on improving their brand presence by resonating with their audience. This line of research could help further refine strategies for creating lasting and credible personal brands in the rapidly evolving digital landscape. This study contributes to the understanding of effective content creation for personal branding on social media, specifically Instagram. This is what attracts the researchers to study it and becomes the focus of problems in research related to the use of Instagram as a medium to build and improve personal branding.